2016
DOI: 10.1002/2016gl067745
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced haze pollution by black carbon in megacities in China

Abstract: Aerosol‐planetary boundary layer (PBL) interactions have been found to enhance air pollution in megacities in China. We show that black carbon (BC) aerosols play the key role in modifying the PBL meteorology and hence enhancing the haze pollution. With model simulations and data analysis from various field observations in December 2013, we demonstrate that BC induces heating in the PBL, particularly in the upper PBL, and the resulting decreased surface heat flux substantially depresses the development of PBL a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
506
4
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 686 publications
(545 citation statements)
references
References 38 publications
(61 reference statements)
31
506
4
4
Order By: Relevance
“…3.3, the SSA was low in July and August, and that was attributed to absorbing particles from biomass burning. Ding et al (2016) found that large quantities of black carbon can be emitted from biomass burning in the YRD during the summer, and because these particles strongly absorb at infrared wavelengths, they can cause a heating up of the atmosphere, resulting in lower negative DARF-TOA. Indeed, the positive DARF-TOA values we found under clear conditions from April to October were mainly due to the effects of strongly absorbing particles; that is, the SSAs at 440 nm were < 0.80, and they showed a strong decrease with wavelength (not shown here) when DARF-TOA values were positive.…”
Section: Aerosol Optical Properties: Aaod and Aaementioning
confidence: 99%
See 1 more Smart Citation
“…3.3, the SSA was low in July and August, and that was attributed to absorbing particles from biomass burning. Ding et al (2016) found that large quantities of black carbon can be emitted from biomass burning in the YRD during the summer, and because these particles strongly absorb at infrared wavelengths, they can cause a heating up of the atmosphere, resulting in lower negative DARF-TOA. Indeed, the positive DARF-TOA values we found under clear conditions from April to October were mainly due to the effects of strongly absorbing particles; that is, the SSAs at 440 nm were < 0.80, and they showed a strong decrease with wavelength (not shown here) when DARF-TOA values were positive.…”
Section: Aerosol Optical Properties: Aaod and Aaementioning
confidence: 99%
“…Studies of aerosol optical properties in eastern China have contributed to our understanding of local air quality and regional climate impacts (Duan and Mao, 2007;Pan et al, 2010;Ding et al, 2016). In the YRD, investigations of aerosol optical properties have been conducted in Nanjing, Hefei, Shanghai, Shouxian and Taihu (Zhuang et al, 2014;He et al, 2012; K. H. Cheng et al, 2015;Xia et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Some model simulations proposed that the radiative forcing of black carbon (BC) is comparable to that of methane (Chung and Seinfeld, 2005;Jacobson, 2004), suggesting that BC may be the second most important warming agent (only after CO 2 ) in terms of direct radiative forcing (Jacobson, 2001). Ding et al (2016) found that BC particles play a key role in modifying and heating the planetary boundary layer (PBL) and enhancing the haze pollution, called the "dome effect" of BC, and suggested an urgent need for reducing BC emissions to mitigate the extreme haze pollution in megacities in China. In addition, high concentrations of absorbing aerosols (e.g., BC, brown carbon, and/or dust) over eastern China during winter and spring were found to be the major reason for the observed recent warming trend (Yu et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…BC issue has been noticed in recent years in China, including its temporal variations, emission sources, climate effect (Cao et al, 2006;Cao et al, 2009;Yang et al, 2009;Wang et al, 2017a;Huang et al, 2014) as well as its 'dome effect' in modifying the boundary layer and enhancing haze pollution in megacities (Ding et al, 2016b). 20…”
Section: Pagementioning
confidence: 99%